The Middle Class Is Synonymous with Corruption in Sub-Sahara Africa - Norman, Ishmael D.; Aviisah, Mark A.; Awiah, Blandina M.; Kweku, Margaret; Binka, Fred N. (Scientific Research Publishing, 2016)
Objective: We investigated middle class’ contribution to corruption in Sub-Sahara Africa. We assessed the effect of how the upward mobility of the middle class would be driven, if the underlying socio-economic conditions were to be improved. The third inquiry focused on whether the people appeared conflicted, where they seemed to have two separate personalities of “one for Caesar” and the “other for God” in the conduct of their official and professional duties. We finally assessed if exposure to a good dose of ethics would mitigate corrupt practices. Method: Using Ghana as the case study, we conducted a review of the literature on corruption in Sub-Sahara to assess if the phenomenon was growing with the middle class. These included published research on corruption and on the middle class in Sub-Sahara Africa. Grey literature, various government commissions’ report after investigations into allegations and cases of corruption, as well as reports of the national Public Accounts Commission and those of the Controller Accountant General’s available to the public on the internet was reviewed. All the findings were grouped into their respective units and the issues summarized and interpreted. Result: The middle class are the gate-keepers of policy design, implementation, monitoring and evaluation. They control service delivery and occupy middle to upper level management positions in public and private enterprises. They provide the bulk of the academic and intellectual resources and capacities for education. The effect of their conduct in professional roles may substantially contribute to the erosion of responsible moral conduct and professional ethics in the delivery of services and in the lives of the population. Discussion: The middle class is engaged in a deadly game of “catching up with the Mensahs”. Whatever Mensah has, even if he acquires it illegally and through corrupt means, everyone in Mensah’s neighborhood irrespective of religion, social antecedents and professional ethics, wants to be just like Mensah. Conclusion: Such conduct does not consider the moral and legal duty of care of the middle class to the population guided by ethical principles.
Keywords: Corruption; Middle Class Role; Ghana; Sub-Saharan Africa